Successful hiatal hernia repair with Nissen fundoplication by laparoscopic approach: a case report - Francis Celeste; I Made Yudi Mahardika; Wifanto Saditya Jeo (Intisari Sains Medis, 2020)
Background: Hiatus hernias represent a herniation of viscera, most commonly the stomach, into the mediastinum through the esophageal hiatus of the diaphragm.There are two main classifications, sliding hernias and paraesophageal hernias. This case study aims to evaluate the successful hiatal hernia repair with Nissen fundoplication by a laparoscopic approach.Case Presentation: We present a case of a 60-year-old male who presented with recurrent abdominal discomfort 6 months prior to the consultation. This was accompanied by loose stools, bloating, nausea, and vomiting. An initial diagnosis of Gastroesophageal Reflux Disease (GERD) was made. Conservative treatment was initiated with limited success. Endoscopy was then performed, revealing a hiatal hernia. Surgical intervention was then chosen as a therapeutic option via a laparoscopic approach and additional Nissen fundoplication with favorable outcomes.Conclusion: Symptomatic paraesophageal hernias are indicated for surgical repair.Paraesophageal hernias can be repaired transthoracically and transabdominal. Repairs via the transabdominal route can be performed with an open approach or laparoscopically, with the laparoscopic approach suggesting lower mortality and morbidity. Nissen fundoplication has been proven as an effective measure in GERD's control and in maintaining an intra-abdominal location of the gastroesophageal junction (GEJ).